SOURCE STUDIES OF THE CONTRIBUTION OF HOSTELS (IN PERSIAN LANGUAGE IS KHANAQAH) AND HOSPITALS TO THE SUPREME EDUCATION SYSTEM OF MOVAROUNNAHR AND KHORASAN - Imamov Ulug’bek Ismailovich (Web of Journals Publishing, 2023)
Before the Timurids and during their time, mosques and khanaqahs were built next to madrassas. According to the ideology of the Shura, the khanqah in scientific works was often assessed as a place where mention was performed only by dervishes and qalandars, sheikhs and ascetics. In the “Uzbek Soviet Encyclopedia” the following is written about it: “Khonaka is a khanaqah where sheikhs and dervishes perform mention in a mosque. The mosque was built in the style of part of a mausoleum as a place for overnight stays for dervishes and pilgrims. The center of dervish associations were the large halls of large khanaqahs, around which there were khanaqahs for pilgrims.
Keywords: Hostel, hospital, Sufism, spiritual and educational meetings, talented mudarris, dervish, Debates and discussions.